Proposed new interior design scheme of Mai Beaute Spa at Lot 4388 - 4390 Hexbon Industries (M) Sdn. Bhd. 677 Jalan Melaka Raya 8, Taman Melaka Raya, 75000 Melaka / Noor Baidzurah Mahfodz - Mahfodz, Noor Baidzurah (Faculty of Architecture, Planning and Surveying, 2011)
Final project for the students of Diploma in Interior Design is a the symbol of student knowledge about all aspects of the more widely used in interior design has learned from basic to complete projects that have been selected. The project that had been chosen for this final project is to propose a new interior design for the interior of Maibeaute spa that is situated at Lot 4388-4390 Hexbon Industries (M) Sdn. Bhd. 677 Jalan Melaka Raya 8, Taman Melaka Raya, 75000 Melaka. This proposed spa is to attract users, mostly on women to try for their treatments offered in Maibeaute spa such as on head, face, body and foot treatment. If we flash back old days, not many people go to spa to do treatment because they consider spa is only connect with higher-up. But nowadays, spa is very different situation with earlier period because they was plently spa which offers treatment to all plebeian to upper crust. The target market for the users of this spa range product is fully women from all age and classes, that are concern about their look and appearances, not forgetting to find those who are interested in trying a modern malay-based spa treatment. Concept and image that had been chosen not only must be suitable with the clients as both of it would reflect the client itself, but at the same time it would give a positive impact and to increase the faith in the customers and the workers in Maibeaute spa. Other than that, the chosen design style for Maibeaute is based on nature design and Modern, goes all the way with the client’s needs as they want the spa have new design and would attract the customers with different image that they would only get in Maibeaute. Before getting a desired design that is suitable with the client’s needs, some data analysis should be done where these analysis is on types of customers to attend the session, types of services offered, products of the brand, spaces to be concluded in the proposed area, operation time and information about other spas that use the same system in management, as the proposed spa. Some of the gained information of the study is through interviews, printed media, internet, observation, and through the result from the case study either locally or internationally.